Trabeculectomy versus Xen gel implant for the treatment of open-angle glaucoma: a 3-year retrospective analysis. Issue 1 (4th January 2022) - Cappelli, Francesca; Cutolo, Carlo Alberto; Olivari, Sara; Testa, Valeria; Sindaco, Daniele; Pizzorno, Chiara; Ciccione, Sara; Traaverso, Carlo Enrico; Iester, Michele
Abstract : Objective: To compare the two surgical techniques in terms of efficacy, safety, and postoperative management over 36 months of follow-up. Methods: This retrospective clinical cohort study compared the outcome of trabeculectomy surgery and Xen gel implant in patients having uncontrolled glaucoma. Patients were recruited using the following inclusion criteria: uncontrolled intraocular pressure (IOP) on maximally tolerated medical therapy, healthy conjunctiva freely mobile in the superior sector, open-angle, glaucomatous visual field damage, full follow upfollow-up of at least 36 months. Thirty-four patients were submitted to trabeculectomy and 34 to Xen gel implant. We set the lower limit at 6mmHg mm Hg and the upper limit ≤12 mm Hg for criteria A, upper limit to ≤15 mm Hg for criteria B and upper limit ≤18 mm Hg for criteria C. Criteria for success have been characterizedcharacterised according to whether or not this has been achieved without (complete success) or with IOP -lowering medications (qualified success). Results: For all survival curves, trabeculectomy was superior to Xen gel implant. When considering complete success, the log-rank test for criteria A was statistically significant (pp=0.006), marginally significant for criteria B (pp=0.065) and not significant for criteria C (pp=0.23). When qualified success was considered, trabeculectomy was superior to Xen gel for criteria A, B, and C (pp=0.012, pp=0.033 and pp=0.025, respectively). Higher number of post-operative flat chamber and bleb leakage was observed in the trabeculectomy group. Conclusion: Xen gel implant techniques offer a better safety profile but a lower IOP reduction compared to compared with the gold -standard technique.